2021
DOI: 10.4103/jfmpc.jfmpc_1249_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID–19 and police personnel

Abstract: Introduction: COVID-19 has ensured that countries enforced complete lock down to prevent the spread of infection. Despite millions of people working from home during this pandemic situation, police personnel 'the front line workers' who deal with the general population to ensure their safety and wellbeing are at risk of stress and other mental health problems in addition to the risk of infection itself. Aim: The aim of this study is to explore the perception of police p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Another study found protective service workers were impacted psychologically similarly to the general population. However, they were worried about passing the infection on to others, and making them follow COVID-19 regulations such as staying home added to their stress [12]. A study that included armed forces and specialized state security forces found that while 26.4% of the participants felt a current need for psychological help, 52.6% felt they would probably need psychological help if a new wave of the pandemic were to arise.…”
Section: Protective Service Occupationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study found protective service workers were impacted psychologically similarly to the general population. However, they were worried about passing the infection on to others, and making them follow COVID-19 regulations such as staying home added to their stress [12]. A study that included armed forces and specialized state security forces found that while 26.4% of the participants felt a current need for psychological help, 52.6% felt they would probably need psychological help if a new wave of the pandemic were to arise.…”
Section: Protective Service Occupationsmentioning
confidence: 99%
“…Moreover, many had to reduce their hours or leave their job to look after their children because they could not afford childcare costs (as schools were closed) with their low-paying jobs [38]. Police personnel in one study expressed their concerns about being unable to spend time with their family during the lockdown [12].…”
Section: Being Unable To Care For Children and See Familiesmentioning
confidence: 99%
See 2 more Smart Citations